(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
Known since the since the twenties of the nineteenth century, when the temple was completely taken to the light and rebuilt to host the “Museo patrio”, the Capitolium of Brescia has been object of many studies, first of all the volume “Museo bresciano illustrato”, published in 1838 to the end of investigations carried out between 1823 and 1826. In spite of the interest from many scholars of the Roman architecture in Cisalpine, the temple has never been studied systematically, even if during the seventies Antonio Frova, with Giuliana Cavalieri Manasse and Maria Pia Rossignani, started to study and to catalog the architectural material publishing first results in occasion of the nineteenth centenary of the Temple’s dedication in the 1973. In anticipation of the publication of the last field investigations and of the researches that recently have been realized both on the Capitolium and on the Republican Sanctuary, expected in 2013, this paper aims to present architectural blocks and fragments of the architectural decoration in a catalogue resulted by a census both of the pieces replace in situ and of those ones still on the ground.